Fast shear wave dynamics of a 3D-printed acrylonitrile-butadiene-styrene sample - Volodarskii, A.; Morokov, E.; Odina, N.; Kokshaiskii, A.; Korobov, A. (Russian physics journal, 2025)
The results of experimental studies of fast dynamics (dependence of transmitted elastic wave amplitude and velocity on pump amplitude) of longitudinal and transverse elastic waves in a 3D-printed polyacrylonitrile-butadiene-styrene (ABS) sample are reported. The measurements are carried out using the echo-pulse method in the frequency range from 500 to 900 kHz. It is shown that the pump amplitude dependence of the wave velocity variation is stronger for longitudinal waves, while the dependence of the passing wave amplitude on the pump amplitude is stronger for transverse waves with different polarizations. Both cases demonstrate a nonlinear nature of the dependence. Based on the data on the velocity of longitudinal and transverse waves, the estimates of nonlinear changes in the elastic modulus are obtained.